PERAN KEPOLISIAN DALAM MENANGGULANGI TINDAK PIDANA PENGANIAYAAN DITINJAU DARI HUKUM PIDANA ISLAM (STUDI KASUS DI KEPOLISIAN SEKTOR PEMULUTAN KABUPATEN OGAN ILIR) - zoliya atina; Armasito Armasito (Tazir, 2023)
ABSTRACT Crime is an act that often occurs in the community, one of which occurs in the Legal Area of ​​the Pemulutan Police. This is very disturbing and disturbing the problems and security of the community. Therefore, the role of the police is needed to make countermeasures in order to minimize the acts of persecution that occur. The formulation of the problem in this study is how the role of the police in tackling criminal acts at the Pemulutan Police of Ogan Ilir Regency and how Islamic criminal law is on the role of the Police in tackling criminal acts at the Pemulutan Police of Ogan Ilir Regency. The method used in this research is empirical juridical with qualitative type. The conclusion of this study is that the role of the police in tackling criminal acts at the Polsek Pemulutan is carried out with two efforts, namely preventive efforts and repressive efforts. Prevention is carried out in the form of general efforts, namely socialization of the culture of prohibiting violence, increasing happiness, and the dangers of drug and alcohol efforts. Then repressive efforts are tackling the case settlement process from the investigation and investigation of the Public Prosecutor's case to resolve the trial problem and the settlement of case settlement with a peace system (restorative justice) and the settlement of case settlement. Then the second is that the role of the police in tackling criminal acts at the Pemulutan Police of Ogan Ilir Regency is carried out in accordance with Islamic criminal law as has been implemented by Rasulullah SAW in terms of law, which aims to carry out amar ma'ruf nahi munkar and to achieve the objectives of criminal law. Islam as it can maintain life as Maqāsid Ash-Syarī'aḥ or Al-Maqasid Al-Khomsah, namely hif annafs (maintaining the soul), Hifzh-dīn (maintaining religion), hif-'aql (maintaining reason), hifzh an-nasb (maintaining offspring) and hifz al-māl (maintaining property). Keywords: Islamic Criminal Law, Countermeasures, Role of Police, Crime of Persecution